EMOTIONAL AND EXPRESSIVE FEATURES OF PHRASEOLOGY ABOUT PATIENCE AND ENDURANCE - Raxmanova Sarvinoz Alisherovna (Western European Studies, 2025)
This article is devoted to the topic "Emotional and expressive features of phraseology about patience and endurance" and analyzes the specific emotional and expressive aspects of the words patience and endurance on the example of phraseological units. The article examines the importance of phraseology about patience and endurance in linguistics, their connection with spiritual and moral, psychological states, and the emotional variety expressed through language. In particular, the semantic and stylistic aspects of phraseologisms, how they express relationships between people, internal mental states and emotions are analyzed
Keywords: Patience and endurance; Phraseological units; Emotional characteristics